Long-Term Post-COVID-19 Associated Oral Inflammatory Sequelae - Alfaifi, Areej; Sultan, Ahmed S.; Montelongo-Jauregui, Daniel; Meiller, Timothy F.; Jabra-Rizk, Mary Ann (Frontiers in Cellular and Infection Microbiology, 2022)
The oral cavity remains an underappreciated site for SARS-CoV-2 infection despite the myriad oral conditions observed in COVID-19 patients. Recently, replicating SARS-CoV-2 was found inside salivary epithelial cells resulting in inflammation and atrophy of salivary glands. Saliva possesses healing properties crucial for maintaining the health of the oral mucosa. Specifically, salivary antimicrobial peptides, most notable, histatin-5 exclusively produced in salivary glands, plays a vital role in innate immunity against colonizing microbial species. The demonstration of SARS-CoV-2 destruction of gland tissue where histatin-5 is produced strongly indicate that histatin-5 production is compromised due to COVID-19. Here we present a case of a patient presenting with unexplained chronic oral dysesthesia and dysgeusia post-recovery from COVID-19. To explore potential physiological mechanisms behind the symptoms, we comparatively analyzed saliva samples from the patient and matched healthy subject for histatin-5 and key cytokines. Findings demonstrated significantly reduced histatin-5 levels in patient’s saliva and activation of the Th17 inflammatory pathway. As histatin-5 exhibits potent activity against the opportunistic oral pathogen Candida albicans, we evaluated saliva potency against C. albicans ex vivo. Compared to control, patient saliva exhibited significantly reduced anti-candidal efficacy. Although speculative, based on history and salivary analysis we hypothesize that salivary histatin-5 production may be compromised due to SARS-CoV-2 mediated salivary gland destruction. With the current lack of emphasis on implications of COVID-19 on oral health, this report may provide lacking mechanistic insights that may lead to reassessment of risks for oral opportunistic infections and mucosal inflammatory processes in acutely-ill and recovered COVID-19 patients